Optimal DG Placement and Sizing for Voltage Stability Improvement Using Backtracking Search Algorithm - Ruhaizad, Ishak; Azah, Mohamed; Abdalla, Ahmed N.; Mohd Zamri, Che Wanik (2014)
The increase in power demand and limitation of transmission capacities have led to strong concern among electrical power industrials. The large deployement of distributed generation (DG) sources in distribution network can be an efficient solution to overcome power system technical problems and economical challenges. Unlike centralized electrical generation, the DGs generate electrical energy near to the load centres with small generating capacity. Installing DG may influence power system stability and losses. To maximize such benefits, the optimal location and sizing of DGs are very important. This paper presents a method to identify optimal DG location based on maximum power stability index while minimization of real power loss and also DG cost is considered in optimizing the DG size. A new evolutionary algorithm known as backtracking search algorithm (BSA) is opted in solving the optimization problem. The applicability of proposed method is verified using the IEEE 30-bus transmission network.